The impact of interactive video-based exercise on quality of life among pregnant women in Indonesia: A pilot study - Marfuah, Dewi; Sansuwito, Tukimin bin; Ayakannu, Rathimalar (Faculty of Nursing Universitas Padjadjaran, 2025)
Background: Pregnant women experience lower quality of life compared to the general population and experience a decrease in their quality of life as their pregnancy progresses. Video interactive provides an interesting and interactive environment, so participants would be more likely to enjoy completing their physical activity regimen. Objectives: This study aimed to determine the impact of video interactive-based exercise on quality of life among pregnant women in Indonesia. Methods: A quasi-experimental study was carried out in Bandung, West Java, Indonesia from August 2023 to January 2024. The intervention and control groups involved healthy pregnant women aged above 18 years old, second trimester pregnant, advised by healthcare, literate, and willing to participate in physical activity. The study involved 264 pregnant women, with a response rate of 96%. Data was collected before (T0), immediately after (T1), and 2 weeks after the intervention (T2). The videos covered combination of exercise program for pregnant women, including warm-up, main phase (with an aerobic element, followed by strength and endurance exercises) and final stretching and relaxation. quality of life was measure using quality of life Gravidarum. The analysis was evaluated using repeated ANOVA test and difference-in-difference estimate. Results: After a two-week follow-up, the intervention group showed a substantial increase in quality of life scores, with a moderate level of impact (effect size= 0.39). The difference-in-difference estimate showed a modest increase of 3.57 percentage points between groups. Conclusion: The study demonstrated that video interactive exercise significantly improved the quality of life for pregnant women, indicating the potential for encouraging their participation in such activities.